24‐5L: Late‐News Paper: Ultra Durable and Foldable AMOLED Display Capable of Withstanding One Million Folding Cycles. Issue 1 (May 2016) - Lee, Meng‐Ting; Wang, Cheng‐Liang; Chan, Chi‐Shun; Fu, Ching‐Chieh; Chen, Chung‐Chia; Lin, Kuan‐Heng; Huang, Wen‐Chung; Chen, Yi‐Hong; Su, Wei‐Jen; Chang, Cheng‐Hao; Tu, Chia‐Hsu; Lu, Pei‐Hua; et al.
Abstract : A highly durable and foldable AMOLED display with a symmetric panel stacking (SPS) design and touch functionality was demonstrated to surpass 1 million folding cycles with no damage to the TFT, OLED and TFE layers. The S/N ratio of the touch function was improved using a metal mesh touch sensor.